Proteoglycan Dysfunction: A Common Link Between Intervertebral Disc Degeneration and Skeletal Dysplasia - Kimheak Sao; Makarand V. Risbud (Neurospine, 2024)
Proteoglycans through their sulfated glycosaminoglycans regulate cell-matrix signaling during tissue development, regeneration, and degeneration processes. Large extracellular proteoglycans such as aggrecan, versican, and perlecan are especially important for the structural integrity of the intervertebral disc and cartilage during development. In these tissues, proteoglycans are responsible for hydration, joint flexibility, and the absorption of mechanical loads. Loss or reduction of these molecules can lead to disc degeneration and skeletal dysplasia, evident from loss of disc height or defects in skeletal development respectively. In this review, we discuss the common proteoglycans found in the disc and cartilage and elaborate on various murine models and skeletal dysplasias in humans to highlight how their absence and/or aberrant expression causes accelerated disc degeneration and developmental defects.